Learning Experiences of Students Who Are Hard of Hearing in Higher Education: Case Study of a South African University - Bell, Diane (Social Inclusion, 2018)
Students who are hard of hearing (HOH) are being granted access to university increasingly, yet they remain significantly under-represented and under-supported, often resulting in poor academic outcomes with elevated levels of attrition. This situation places a growing obligation on universities to improve the support provided to these students in order to have a positive influence on their overall academic experience and eventual economic independence. This trend is relevant to South Africa, where Higher Education Institutions (HEIs) are accepting and registering students with a hearing loss but are not providing adequate academic support and inclusive curricula. Furthermore, in South Africa, almost no research has been conducted concerning students who are HOH in higher education regarding their teaching and learning needs or the coping strategies which they use to survive academically. However, what is known is that, of those HOH students who do enter higher education, many do not graduate successfully (up to 75%) and, of those that do graduate, many continue to be excluded from professions. The aims of this article were to report on the teaching and learning experiences of students who are HOH at a South African university, who prefer to make use of spoken language, to share the daily barriers with which they are faced, and to provide recommendations for teaching and learning, as well as curricula transformation. This study adds to the existing body of knowledge on this topic in South Africa and could be relevant in similar contexts.